Prognostic Gene Expression Signature for Age-Related Hearing Loss - Peng, Lu; Li, Nianshen; Huang, Zhanrong; Qiu, Chunqin; Yin, Shihua (Frontiers in Medicine, 2022)
Background Our study aimed to determine the pathological mechanism of presbycusis at the molecular level, and determine potential biomarkers for the same. Methods Differentially expressed genes (DEGs) for presbycusis were obtained by analyzing the microarray data sets (GSE6045 and GSE49543) downloaded from the Gene Expression Omnibus (GEO). Gene ontology (GO), Kyoto Encyclopedia of Genes and Genome (KEGG) pathway, and protein-protein interaction (PPI) network analyses, and Gene Set Enrichment Analysis (GSEA) were performed to analyze the biological functions, molecular pathways, autophagy-related molecular markers, and the immune microenvironment of the DEGs in presbycusis. Then the prognostic roles of the hub genes were analyzed and verified in vivo. Results In the old mild hearing loss group (27.7 ± 3.4 months old), 27 down-regulated and 99 up-regulated genes were significantly differentially expressed compared with those in the young control group (3.5 ± 0.4 months old). In the old severe hearing loss group (30.6 ± 1.9 months old), 131 down-regulated and 89 up-regulated genes were significantly differentially expressed compared with those in the young control group. The results of the GO, GSEA, KEGG pathway, and immune infiltration analyses showed that the enrichment terms were mainly focused on immune response in mild presbycusis, and immune response and cell death in severe presbycusis. In the PPI network, autophagy-related genes ATG5, ATG7 showed the highest node scores in mild presbycusis; whereas MTOR, BECN1 showed the highest scores in severe presbycusis. In the GSE49543 data set, four genes (Ywhag, Mapre2, Fgf1, Acss2) were used to construct the prognostic model, and those four genes were significantly up-regulated in the rat model of presbycusis. Conclusion Our study is the first to report the difference in autophagy factors and immune microenvironment among different degrees of hearing loss in presbycusis. Furthermore, we provide the prognostic gene expression signature for age-related hearing loss, intending to develop preventative therapies.